2010
DOI: 10.24839/1089-4136.jn15.4.186
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Faith: Comparing Religiousness and Spirituality to Self-Construal and Religious Orientation

Abstract: We examined the potential influence of family characteristics on ego identity and self-esteem among emerging adults. College students (N = 210, M = 19.52 years, 65% women) completed measures of self-esteem, ego-identity, and family functioning (General Family Functioning, Communication, Roles, Affective Responsiveness, Affective Involvement, and Behavior Control). In a multiple regression analysis, self-esteem was predicted by ego identity, general family functioning, and gender. Similarly, when ego-identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…First of all, most past research studied how IRO alone influence EI without taking into consideration of spirituality. Dooley et al [56], suggested that although there might be a clear distinction between the definition of religiosity and spirituality by the scholar, most participants did not measure their religiosity based on ceremonial attendance or the degree to which they fit into their religious affiliation. Furthermore, past research showed that although there are arguments that spirituality is different from religion, the distinction is still not very well-defined [57].…”
Section: Study Twomentioning
confidence: 99%
See 3 more Smart Citations
“…First of all, most past research studied how IRO alone influence EI without taking into consideration of spirituality. Dooley et al [56], suggested that although there might be a clear distinction between the definition of religiosity and spirituality by the scholar, most participants did not measure their religiosity based on ceremonial attendance or the degree to which they fit into their religious affiliation. Furthermore, past research showed that although there are arguments that spirituality is different from religion, the distinction is still not very well-defined [57].…”
Section: Study Twomentioning
confidence: 99%
“…It was suggested that people with higher IRO tend to have higher spiritual maturity which helps them in perceiving and understanding emotions [43]. Thus, as they were participating in studies which investigate IRO as the only predictor of EI (where spirituality was not controlled for), they might take spirituality into consideration unconsciously since the terms religiosity and spirituality are often used interchangeably [56].…”
Section: Study Twomentioning
confidence: 99%
See 2 more Smart Citations